Pengaruh Profitabilitas, Leverage Dan Ukuran Perusahaan Terhadap Penghindaran Pajak Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Periode 2018-2022 (Sektor Industri Barang Konsumsi) - Tambunan, Ruth; Rofingatun, Siti; Bleskadit, Novalia Herlina (JURNAL AKUNTANSI DAN KEUANGAN DAERAH, 2023)
The purpose of this analysis is to find out the effect of profitabilities, leverage and company size on tax avoidance in manufacturing companies listed on the Indonesia Stock Exchange for the period 2018 - 2022. The population that is used in this study is manufacturing companies in the consumer goods industry sub-sector listed on the Indonesia Stock Exchange for the period 2018 - 2022. The sampling method in this study used purposive sampling according to predetermined criteria. The number of samples collected is 150 samples and with outliers becomes 120 samples. The analysis technique that is used in this research is multiple linear regression analysis using the help of SPSS version 21 software. Based on the results of research using SPSS as a testing tool, it shows that partially Profitability and Company Size have a significant negative effect on tax avoidance. While Leverage has no effect on tax avoidance.